Ground response to rolling dynamic compaction. Issue 2 (19th April 2019) - Scott, B.; Jaksa, M.; Mitchell, P.
Abstract : Rolling dynamic compaction (RDC) is typically used for improving ground in situ or compacting fill in thick lifts. In many project applications, the effects of RDC are verified by way of testing that is undertaken pre- and/or post-compaction. This study presents results from a full-scale field trial that involved placing an earth pressure cell (EPC) and accelerometers at a depth of 0·7 m within a 1·5 m thick layer of homogeneous sandy gravel to measure the response to RDC in real-time. Double integration of acceleration–time data enabled settlement to be inferred, while the EPC measured the change in stress due to impact. The maximum change in vertical stress recorded over the 80 passes undertaken was approximately 1100 kPa. During a typical module impact, the loading and unloading response occurred over a duration of approximately 0·05 s. The acceleration response of RDC was measured in three orthogonal directions, with the vertical accelerations dominant.